Nutrient partitioning and stoichiometry in soybean: A synthesis-analysis - Tamagno, S. (2017)
On-farm attainable soybean yields are primarily limited by nutrient and water supply. High-yielding soybeans is related to high nutrient uptake. A proposed theoretical framework underpinning yield formation includes plant nitrogen (N) uptake, N harvest index (NHI), and N seed concentration (%Nseeds). The objectives of this study were focused on (i) investigating the effect of NHI and %Nseed on yield-to-uptake relation for N, and (ii) analyzing dry mass and N partitioning and extending this analysis to phosphorous (P) and potassium (K) uptake and (iii) studying the influence of specific seed:stover ratios on the relationship of N with P, and K uptake. Metadata on yield, nutrient uptake and specific-organ nutrient concentration (%nutrient) was summarized from experiments located in three different environments: Indiana, Kansas (both US), and Argentina (herein termed as IN, KS, and ARG, respectively). The main outcomes from this research were: 1) the yield-to-uptake relation for N was primarily explained by NHI; 2) the algebraic model proposed by Sinclair (1998), that includes each specific-organ %nutrient explained consistently nutrient (N, P or K) HI as a function of HI with different trend, and 3) plant nutrient ratios were primarily governed by vegetative %nutrient (stover fraction), acting as a nutrient reservoir or supply depending on the demand of nutrient in the seed. Further research on the nutrient and biomass partitioning should focus on examining the NHI:HI relationship under varying genotype x environment x management interaction.